2019
DOI: 10.2147/cmar.s193325
|View full text |Cite
|
Sign up to set email alerts
|

<p>Early detection of prostate cancer using prostate-specific antigen testing: an empirical evaluation among general practitioners and urologists</p>

Abstract: Background: Prostate cancer (PCa) is the most frequent cancer and the third leading cause of cancer death among German men. One option for PCa early detection is prostate-specific antigen (PSA) testing, which is still under debate regarding its risk benefits. Besides recommendations on the early PCa detection, daily practice on PSA testing varies in, for example, information communication and usage of the test. This pilot study assessed potential differences between general practitioners (GPs) and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 37 publications
0
16
1
Order By: Relevance
“…A high density of related specialist physicians had null or even a negative association with screening utilization in our study. This is in contrast to a German online survey where PSA testing was judged as useful by all urologists but only by half of the general practitioners, and where PSA testing practices varied between both clinician groups [ 50 ]. Higher PSA screening rates were also seen in regions where the primary care specialist was unlikely to be the predominant physician for ambulatory visits [ 22 ].…”
Section: Discussionmentioning
confidence: 75%
“…A high density of related specialist physicians had null or even a negative association with screening utilization in our study. This is in contrast to a German online survey where PSA testing was judged as useful by all urologists but only by half of the general practitioners, and where PSA testing practices varied between both clinician groups [ 50 ]. Higher PSA screening rates were also seen in regions where the primary care specialist was unlikely to be the predominant physician for ambulatory visits [ 22 ].…”
Section: Discussionmentioning
confidence: 75%
“…The higher PCa incidence rates in Lower Saxony than in Groningen identified here could be partly explained by the more intensive PSA testing recommendations in the German S3 guidelines compared with the Dutch guidelines (24,26). This possibility is supported by the fact that all urologists surveyed in Lower Saxony claimed to have detailed knowledge of the S3 guidelines (33). The results of a survey conducted in the northeast of the Netherlands also support this possibility by stating that clinical PSA testing in primary care generally seems to be consistent with the relevant guideline for Dutch GPs that is restrictive to PSA testing (34,35).…”
Section: Discussionmentioning
confidence: 94%
“…The reason for this remains unclear, as do the reports by some of our respondents that they adopt their own (unsuitable) criteria and PSA cut-off values for when not to refer a patient to a urologist. In Lower Saxony, Germany, evidence has also been published showing that GPs and urologists did not treat patients in accordance with established guidelines on prostate cancer [ 22 ]. A systematic review looking at the state of PSA testing policies worldwide revealed significant variation in follow-up policies after a normal or raised PSA level, and that this is often discordant with the available practice guidelines [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the questionnaire in this project was conducted in the context of a binational project, a German version of the questionnaire was translated into Dutch. Formal back and forwards translations were performed by native speakers of both German and Dutch [ 22 ]. After translation, the questionnaire was adapted to the Dutch prostate cancer guidelines and the Dutch health care system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation